2013
DOI: 10.1021/es304552b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adaptation on Flex-Fuel Vehicle Emissions When Fueled with E40

Abstract: Nine flex-fuel vehicles meeting Tier 1, light duty vehicle-low emission vehicle (LDV-LEV), light duty truck 2-LEV (LDT2-LEV), and Tier 2 emission standards were tested over hot-start and cold-start three-phase LA92 cycles for nonmethane organic gases, ethanol, acetaldehyde, formaldehyde, acetone, nitrous oxide, nitrogen oxides (NO(x)), carbon monoxide (CO), and carbon dioxide (CO(2)), as well as fuel economy. Emissions were measured immediately after refueling with E40. The vehicles had previously been adapted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 10 publications
4
40
0
Order By: Relevance
“…Additionally, biodiesel is an easy fuel shift, as it can be used pure or mixed with petroleum‐based diesel fuel,58 as both conventional petroleum‐based and FAME‐based biodiesels have similar physical properties, heating values, and cetane numbers 3. 9, 10 FAME‐based biodiesels are also biodegradable, less toxic, have low aromatic and sulfur contents, and result in lower overall carbon emissions than petroleum‐based diesels 11. 12 These factors make biodiesel an ecofriendly and renewable alternative to petroleum‐based fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, biodiesel is an easy fuel shift, as it can be used pure or mixed with petroleum‐based diesel fuel,58 as both conventional petroleum‐based and FAME‐based biodiesels have similar physical properties, heating values, and cetane numbers 3. 9, 10 FAME‐based biodiesels are also biodegradable, less toxic, have low aromatic and sulfur contents, and result in lower overall carbon emissions than petroleum‐based diesels 11. 12 These factors make biodiesel an ecofriendly and renewable alternative to petroleum‐based fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of butanol, acetaldehyde can also be formed through β-scission of aC 4 H 8 OH [52]. Previous studies have concluded that the addition of ethanol and butanol in fuel blends could cause higher acetaldehyde emissions [48,53,54]. Figure 5b presents the impact of the equivalence ratio on acetaldehyde emission for all test fuels.…”
Section: Acetaldehydementioning
confidence: 97%
“…Variability in emission rates when comparing vehicles of different manufacturers is because of differences in FFV engine control strategies (Yanowitz et al 2013). FFV engines have sensors to analyze the fuel mixture and adjust the fuel injection and timing.…”
Section: Inter-vehicle Variabilitymentioning
confidence: 99%